2004
DOI: 10.1073/pnas.0406756101
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of the 8.1 HLA haplotype in patients with autoimmune myasthenia gravis and thymus hyperplasia

Abstract: The 8.1 haplotype of the HLA complex has been reproducibly associated with several autoimmune diseases and traits, notably with thymus hyperplasia in patients with acquired generalized myasthenia gravis, an autoantibody-mediated disease directed at the muscle acetylcholine receptor. However, the strong linkage disequilibrium across this haplotype has prevented the identification of the causative locus, termed MYAS1. Here, we localized MYAS1 to a 1.2-Mb genome segment by reconstructing haplotypes and assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 45 publications
7
67
0
Order By: Relevance
“…Prior studies had suggested that the class I region has a role in susceptibility (42,43). The current analysis reveals that, compared with the other autoimmune disorders, the genetic role of the MHC in MG is distinctive, consisting of a single signal in the class I region, specifically in the vicinity of the HLA complex protein 5 gene (HCP5) located between MICA and MICB.…”
Section: Discussionmentioning
confidence: 83%
“…Prior studies had suggested that the class I region has a role in susceptibility (42,43). The current analysis reveals that, compared with the other autoimmune disorders, the genetic role of the MHC in MG is distinctive, consisting of a single signal in the class I region, specifically in the vicinity of the HLA complex protein 5 gene (HCP5) located between MICA and MICB.…”
Section: Discussionmentioning
confidence: 83%
“…A wide array of autoimmune phenotypes has been associated with this haplotype, including systemic lupus erythematosus (29), autoimmune hepatitis, and myasthenia gravis (25). Interestingly, recent data suggest that DRB1 is not the primary locus of risk for Myasthenia Gravis (30). Truncated 8.1 haplotypes that lack the DR3 allele are associated with higher levels of acetylcholine receptor autoantibodies in subjects with Myasthenia Gravis, and the primary association with disease appears to lie telomeric to the Class II region.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to chromosome 6 painting, the AF129756 BAC (The Sanger Institute) encompassing most of the class III region was used as a second probe to verify MHC integrity. Genotypes of HLA classical molecules (HLA-A, B, C, DR, and DQ) were verified by the Tissue Typing Laboratory in Oxford (Dr. Barnardo Martin), while the homozygosity and genotypes of microsatellites along the class III region (D6S272, D6S2800, MICA, TNFb, and D6S2789) were checked as described before (Vandiedonck et al 2004). Apart from D6S272, which showed heterozygosity for PGF, all other markers showed the expected genotypes.…”
Section: Lymphoblastoid Cell Lines (Lcl)mentioning
confidence: 99%